2020
DOI: 10.1080/09298215.2019.1708412
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the vocal tract on the attack transients in clarinet playing

Abstract: When playing single-reed woodwind instruments, players can modulate the spectral content of the airflow in their vocal tract, upstream of the vibrating reed. In an empirical study with professional clarinettists (N p = 11), blowing pressure and mouthpiece pressure were measured during the performance of Clarinet Concerto excerpts. By comparing mouth pressure and mouthpiece pressure signals in the time domain, a method to detect instances of vocal tract adjustments was established. Results showed that players t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…This suggests that the success of ST in the altissimo register resulted from the fact that the tongue dorsum was unconstrained to freely lower during note production in the altissimo register. This finding that especially during the altissimo register, the vocal tract shape changes by lowering the tongue dorsum is consistent with the literature discussed in the introduction (Clinch et al, 1982; Fritz & Wolfe, 2005; Gardner & Stone, 2015; Lulich et al, 2017; Pamies-Vila et al, 2020; Scavone et al, 2008; Wheeler, 2010).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This suggests that the success of ST in the altissimo register resulted from the fact that the tongue dorsum was unconstrained to freely lower during note production in the altissimo register. This finding that especially during the altissimo register, the vocal tract shape changes by lowering the tongue dorsum is consistent with the literature discussed in the introduction (Clinch et al, 1982; Fritz & Wolfe, 2005; Gardner & Stone, 2015; Lulich et al, 2017; Pamies-Vila et al, 2020; Scavone et al, 2008; Wheeler, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…Few studies studied the influence of tonguing on playing (Guilleman, 2007; Pamies-Vila et al, 2018; 2020). Pamies-Vila et al (2020) showed that during attacks of a note, especially in the altissimo register, vocal tract adjustments influenced inter-oral pressure, such that the inter-oral pressure and the pressure at the mouthpiece were similar, whereas without adjustment the inter-oral pressure was much smaller. This indicates that the pressure within the vocal tract must be high enough to initiate a note during staccato playing, and one of the techniques players use, is shaping their vocal tract in a certain manner.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted, however, that the blowing system reproduces the real conditions with limitations. These limitations concern the fixed mouth cavity -thus disregarding vocal tract modifications [50]-and the fixed position of the artificial lip. On the other hand, the use of such a system allows repeatable excitation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the «dan huang» is very popular in China, the bure (a wind instrument, which is a type of clarinet) in Mongolia, the «zummara» (the double «clarinet» of the Bedouins, in fact, another version of the classical model of the instrument), is very popular in Saudi Arabia, etc. (PÀMIES-VILÀ;HOFMANN ,2020).…”
Section: Introductionmentioning
confidence: 99%